Entrepreneurship, organization capital and the evolution of the firm - Atsushi Oshima; B. Ravikumar; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 2008)
We view the entrepreneur as an agent who possesses human capital in the form of specific skills or talents. When she starts a firm, her human capital is essential to the firm and it has substantial private value. The entrepreneur transforms her human capital over time into what we call organization capital'. This organization capital can be sold as part of the firm, so the dynamic process of transforming specific human capital into organization capital means that the value of the firm increases over time.
Keywords: L26; D92; 330; organization capital; entrepreneur; Unternehmer; Humankapital; Unternehmensgründung; Unternehmensorganisation; Unternehmensentwicklung; Unternehmenswert; Theorie; Japan